PERAN KIAI DALAM REKONSILIASI SOSIAL PASCA CAROK MASSAL DI BUJUR TENGAH PAMEKASAN MADURA - Ismai Ismail; Moh Wardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
This research is a case study conducted in the Central Bujur of Batumarmar District, Pamekasan Regency Madura. In some cases of carok in Madura, it is often followed by follow-up carok, but due to the role kiai, the carok that occurs in Central Bujur is unique because there is no subsequent carok like other carok. This study is to answer the research focus: (1) What is the role of kiai in social reconciliation post-mass carok in the Central Bujur of Pamekasan Madura, and (2) What is the model of social reconciliation in resolving the social conflict post-mass carok in the Central Bujur of Pamekasan Madura. In collecting data, the researchers agreed to interviews and documentation, while data analysis was carried out by data reduction techniques, data purification, verification and conclusions. From the data analysis, findings were obtained: (1) in the reconciliation kiai play a role as a reference, as a conceptor, as a negotiator and mediator, as well as an executor. (2) a model of social reconciliation based on the theory of human needs theory using economic, religious, and socio-cultural approachs.